Efficiency of Funding Healthcare for Ensuring the Economic Security of a Region - Krivenko, Natalya Vasilyeva; Tsvetkov, Andrey Igorevich (Economy of Regions, 2018)
The social sphere plays an important role in the socio-economic development of the developed countries. The achievement of a high level of education, healthcare, science and culture promotes the economic growth and welfare of the population. Recently, however, the Russian researchers do not pay sufficient attention to the new models of the social services. In this regard, the research of the efficiency of healthcare as a major branch of the social sphere is relevant. Under the conditions of deteriorating socio-demographic situation in Russia, an important component ensuring economic security at the level of the country and regions is the preservation of human potential. This challenge is possible to address, on the one hand, due to an increase in spending on healthcare. On the other hand, it is possible due to progressive transformations of the medical care. Such transformations will increase in return of financial investments and the effectiveness of healthcare services. The purpose of the study is to create an assessment model of healthcare performance as well as of the efficiency of financial investments in the healthcare services using the methods of statistical, system and multivariate analysis as well as economic and mathematical modelling. We define the multicriteria character of the efficiency in healthcare connected with multiple cost-benefit ratios while achieving medical, social, economic effects. We propose a multi-factor dynamic model, integrated indicator of performance, and integral indicator of cost-effectiveness. To test the model, we chose one of the priority directions of the healthcare development - fight against tuberculosis, as it is a threat for socio-demographic and economic security of a region. We have assessed the efficiency of funding and performance indicators on the example of tuberculosis service of the Sverdlovsk region. We have received a positive dynamics of medico-demographic indicators as well as a high economic effect. We have proved the possibility to increase the socio-demographic and economic security of a region achieving medical, social and economic efficiency in the healthcare. This contributes to the preservation of human and labour potential, as well as economic growth. The results of the research can be applied in the healthcare system to adequately assess the performance of medical organizations taking into account the specificity of diseases and the efficiency of financial investments as well as the contribution to the socio-demographic and economic security of a region.